Identify Each Variable to Treat Complex Health Conditions - Ross-Williams, Rhoda L. (International Research in Medical and Health Sciences, 2019)
Medical care for complex health conditions requires medical professionals to identify each variable and determine the cause and effect of each variable. This is necessary to protect the patient from deadly treatments that conflict with complex health conditions like Prader-Willi Syndrome (PWS). This article uses Patient X to demonstrate the need for medical professionals to identify variables and the cause and effect of each variable before treating any of the variables. A complex health condition requires research before treatment to avoid life-threatening outcomes for the patient.